PERFORMANCE OF EXOTIC AND INDIAN POTATO VARIETIES IN GUJARAT FOR PROCESSING INTO FRENCH FRIES - Patel, N. H.; Patel, R N; Singh, S V; Pandey, S K; Patel, J. M.; Patel, S. B. (Potato Journal, 2013)
An evaluation of tuber yield, dry matter and storage behaviour of four Indian and two exotic potato cultivars in the sub-tropical plains of Gujarat established that cv. Kufri Surya having high French fries grade tuber yield, good keeping quality and high dry matter, can be cultivated in this region for processing into French fries.